A critical strategy for Taiwan's cybersecurity: a perspective from critical security studies. Issue 1 (2nd January 2019) - Yau, Hon-min
ABSTRACT: This paper examines Taiwan's cybersecurity from the perspective of Critical Security Studies (CSS), also known as the Welsh School. It eschews a conventional realist approach to cybersecurity and addresses Taiwan's state-centric need while attending to considerations of global cybersecurity. It claims that Taiwan's cybersecurity can be improved without being militarised, zero-sum or confrontational and that one nation's cybersecurity is not necessarily another's insecurity. The paper starts by explaining the decision to bring CSS into the question. Informed by CSS, it moves on to understand how cyberwarfare naturally became the dominant discourse of cybersecurity in Taiwan. It next examines the limitations of 'generally-accepted' assumptions regarding cyberwarfare. Then, the paper explores the problematic effects of cyberwarfare within Taiwan's security context. Finally, it proposes a critical strategy to engage Taiwan's security challenge while avoiding the adverse consequences of implementing cyberwarfare. The paper is a reminder to evaluate Taiwan's cybersecurity in a contemporary and theoretically-grounded framework.